2020
DOI: 10.3389/fmicb.2020.591778
|View full text |Cite
|
Sign up to set email alerts
|

Brd/BET Proteins Influence the Genome-Wide Localization of the Kaposi’s Sarcoma-Associated Herpesvirus and Murine Gammaherpesvirus Major Latency Proteins

Abstract: The rhadinoviruses Kaposi's Sarcoma-associated herpesvirus (KSHV) and murine gammaherpesvirus (MHV-68) persist in infected hosts in a latent state that is characterized by the absence of virus production and by restricted viral gene expression. Their major latency protein, the latency-associated nuclear antigen (kLANA for KSHV and mLANA for MHV-68), is essential for viral genome maintenance and replication and involved in transcriptional regulation. Both kLANA and mLANA interact with cellular chromatin-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 115 publications
0
8
0
Order By: Relevance
“…In this work, authors have shown that treatment with the BET inhibitor I-BET151 displaces kLANA protein, as well as BRD2 and BRD4, from viral and host TSSs. Mutations in mLANA preventing BRD2 and BRD4 binding [158] also have similar consequences [98]. In turn, EBNA1 has been described to interact with BRD4 and this interaction appears to play a critical role in EBNA1-mediated transcriptional activation, as it has been shown that BRD4 silencing leads to a decrease in its transcriptional activity [100].…”
Section: Bet Relation With Virusesmentioning
confidence: 97%
See 1 more Smart Citation
“…In this work, authors have shown that treatment with the BET inhibitor I-BET151 displaces kLANA protein, as well as BRD2 and BRD4, from viral and host TSSs. Mutations in mLANA preventing BRD2 and BRD4 binding [158] also have similar consequences [98]. In turn, EBNA1 has been described to interact with BRD4 and this interaction appears to play a critical role in EBNA1-mediated transcriptional activation, as it has been shown that BRD4 silencing leads to a decrease in its transcriptional activity [100].…”
Section: Bet Relation With Virusesmentioning
confidence: 97%
“…Its homologue in MHV-68, mLANA, is expressed in latency and during lytic replication and its function is essential in the establishment and maintenance of latency [147][148][149][150][151][152] and the EBV homologue, the Epstein-Barr virus nuclear antigen 1 (EBNA1), is involved in the regulation of viral transcription, replication and persistence [153]. Several studies show that kLANA and mLANA interact with a region containing the ET domain of BRD2, BRD3 and BRD4 [94][95][96][97]99], and a recent study has described that the preferential localization of kLANA and mLANA at transcription start sites (TSSs) [154][155][156][157] is due in part to BET proteins [98]. In this work, authors have shown that treatment with the BET inhibitor I-BET151 displaces kLANA protein, as well as BRD2 and BRD4, from viral and host TSSs.…”
Section: Bet Relation With Virusesmentioning
confidence: 99%
“… 203 BRD2 is closely linked to infection by various types of viruses, including Kaposi's sarcoma associated‐herpesvirus, murine herpesvirus68, Epstein–Barr virus, and murine leukemia virus. 204 , 205 , 206 , 207 , 208 , 209 Since the infection of host cells by COVID‐19 mainly depends on the RBD domain of the Spike protein, researchers used RBD binding as a phenotypic readout in a high‐throughput CRISPRi screen to systematically discover significant factors regulating viral infection in host cells. 167 The results demonstrated that knocking out the BRD2 gene effectively prevented RBD binding.…”
Section: Potential Pathogenic Targets Of Sars‐cov‐2 For Antiviral The...mentioning
confidence: 99%
“…Even though the binding sites identified in these studies may partially differ, due to the use of a different cellular systems, they show that LANA binds to a far larger number of sites than previously thought. Moreover, binding is preferentially targeted to euchromatic loci, possibly due to LANA's interactions with the H3K4 methyltransferase hSET1 or with BET [253][254][255][256]. It is also of interest that the expression of genes in the proximity of those binding sites does not seem to be affected, suggesting that methylation mediated silencing may be context specific.…”
Section: Kaposi Sarcoma-associated Herpesvirus (Kshv)mentioning
confidence: 99%